Lifespan : why we age--and why we don't have to - Sinclair, David A., 1969-; LaPlante, Matthew D (Atria Books, 2019)
"From an acclaimed Harvard professor and one of Time's most influential people, this paradigm-shifting book shows how almost everything we think we know about aging is wrong, offers a front-row seat to the amazing global effort to slow, stop, and reverse aging, and calls readers to consider a future where aging can be treated. For decades, experts have believed that we are at the mercy of our genes, and that natural damage to our genes--the kind that inevitably happens as we get older--makes us become sick and grow old. But what if everything you think you know about aging is wrong? What if aging is a disease--and that disease is treatable? In Lifespan, one of the world's foremost experts on aging and genetics reveals a groundbreaking new theory that will forever change the way we think about why we age and what we can do about it. Aging isn't immutable; we can have far more control over it than we realize. This eye-opening and provocative work takes us to the frontlines of research that is pushing the boundaries on our perceived scientific limitations, revealing incredible breakthroughs--many from Dr. David Sinclair's own lab--that demonstrate how we can slow down, or even reverse, the genetic clock. The key is activating newly discovered vitality genes--the decedents of an ancient survival circuit that is both the cause of aging and the key to reversing it. Dr. Sinclair shares the emerging technologies and simple lifestyle changes--such as intermittent fasting, cold exposure, and exercising with the right intensity--that have been shown to help lead to longer lives. Lifespan provides a roadmap for taking charge of our own health destiny and a bold new vision for the future when humankind is able to live to be 100 years young"--